Financial regulation and financial system architecture in Central Europe - Scholtens, Bert (Journal of Banking & Finance, 2000)
At the beginning of the transition, advice to Central European countries with respect to how to set up their financial systems was based on models used in western economies. This paper analyzes the experiences to set up a financial system in Central Europe. The experience in the first transition years (1990–1996) with financial system architecture shows that changes are slow but that the Central European countries tend to catch up more quickly with the western ones in the case of their banking systems than with respect to their stock markets.